Pengaruh Risk Perception dan Kualitas Informasi Akuntansi Terhadap Keputusan Investasi di Masa Pandemi (Studi pada Investor GI BEI FE UNHASY Tebuireng Jombang) - Supriyatna Supriyatna; Rachma Agustina (Behavioral Accounting Journal, 2022)
This study aims to determine the Risk Perception and Quality of Accounting Information on Investment Decisions for Investors at the Investment Gallery of the Indonesia Stock Exchange, Faculty of Economics, Hasyim Asy'ari University, Tebuireng Jombang. The method used in this study is a quantitative research method. The population in this study were 34 respondents. The sampling technique is using a saturated sample technique that makes the entire population as a sample. The results of the study show that: (1) Risk perception of investors in the Indonesia Stock Exchange Investment Gallery, Faculty of Economics, Hasyim Asy'ari University, has no influence on investment decisions during the pandemic, (2) Quality of accounting information on investors in the Indonesia Stock Exchange Investment Gallery, Faculty of Economics, University Hasyim Asy'ari has an influence on investment decisions during the pandemic.